Implementation of LEISA Concept through composting rice straw waste in Subak Telun Ayah, Tegallalang - Muliarta Muli I Nengah; Desak Ketut Tristiana Sukmadewi; Dewa Gede Wiryangga Selangga; I Gede Kariasa; Desak Ayu Diah Prawerti; I Komang Adi Parwata; I Wayan Landra (University of Merdeka Malang, 2022)
In general, many farmers tend to still regard rice straw as waste material that is burned. Burning rice straw is a bad habit because it removes organic matter that contains nutrients needed by plants. As a result, farmers require higher fertilizer costs in the next planting period which is contrary to the concept of Low External Input Sustainable Agriculture (LEISA). Community Service in Subak Telun Ayah aims to increase farmers' knowledge related to the use of compost in rice cultivation and as an effort to reduce inorganic fertilization. The methods used are surveys, interviews, discussions, counseling, and plot demonstrations. Farmers claim to burn rice straw because it is based on the knowledge passed down from generation to generation and it is believed that straw waste is quickly returned to the soil. Farmers do not do composting because they do not know how to compost rice straw. Based on farmers' problems, assistance is carried out by providing training and making demonstration plots. After the mentoring program, farmers are willing to do composting, moreover, it takes 30-35 days and is repeated every 7 days. Farmers' interest in composting is also triggered by the difficulty of obtaining inorganic fertilizers and the rising price of inorganic fertilizers.